A European social agenda: poverty benchmarking and social transfers - A. B. Atkinson (University of Essex, Institute for Social and Economic Research (ISER), 2000)
Development of the social dimension of Europe was advanced by the Lisbon Summit in March 2000, and this paper considers the future direction of social policy. The first step towards a social agenda could take the form of benchmarking, based on national competencies in this field, with Member States learning from best performance in the Union; this step would be parallel to the first phase of the Maastricht process towards macro-economic convergence. Initially, this benchmarking would focus on financial poverty: people living in households with economic resources below the level used by Eurostat (60% of the median in the Member State), with this being accompanied by a measure of child poverty. Social investment in improving labour market skills and employability, or an active welfare state, is an important part of antipoverty policy, but is not a complete substitute for social spending. The European countries which perform best in terms of reducing poverty tend to have higher social spending. Such statistical performance indicators need however to be accompanied by evaluation of the relationship between policy instruments and poverty reduction, showing the trade-off between poverty reduction and social spending at the level of individual policies. Illustrative estimates using EUROMOD suggest that employing universal social transfers to reduce a country's poverty rate from the EU-average of 18% to the best-performing average of 12% would necessitate an increase in social transfers of some 2% of GDP. More targeted schemes may allow sizeable expenditure savings but at the cost of increased disincentives; the design of Europe's social agenda has to confront well-known issues of economic trade-offs; economic and social policy cannot be divorced.
Keywords: I3; 330; Poverty; Social transfers; Social inclusion; Children; Tax-benefit simulation; Verfassungsökonomik; Sozialpolitik; Armutsbekämpfung; EU-Staaten